Integrative Islamic Education: Critical Analysis Study in Islamic Education Institution - Agus Salim; Evita Yuliatul Wahidah; Muhammadong (Universitas Ahmad Dahlan, 2021)
This study examines the complexity of academic problems caused by important dichotomical components. It also analyzes the curriculum dichotomy (among natural, social, general and religion sciences, Furthermore, the research also determines the dichotomy in students cognitive, affective and psychomotoric abilities and in teachers, which includes three aspects, namely intellectual, social and spiritual, in order to achieve an impact on the gap, in theory, practice (process) and output. Due to these reasons, the right solution for solving educational problems is needed. One of the solutions is implementing an integrative Islamic education pattern. This study discusses the paradigm of integration-interconnection education, integrative Islamic education as the dynamics of scientific diversification development, the urgency of integrative Islamic education, the objectives of integrative Islamic education as an educational totality, and components of integrative Islamic education. The result shows that Integrative Islamic Education provides solutions to academic problems in terms of the important components dichotomy in education, which includes the curriculum, students and educators or teachers.